ChemInform Abstract: An Efficient and Straightforward Route to Terminal Vinyl Sulfones via Palladium‐Catalyzed Suzuki Reactions of α‐Bromo Ethenylsulfones. Issue 29 (June 2016) - Fang, Yewen; Yuan, Meijuan; Zhang, Juncong; Zhang, Li; Jin, Xiaoping; Li, Ruifeng; Li, Jinjian
Abstract: An efficient and straightforward method for the preparation of α‐substituted alkenylsulfones via Suzuki reactions of α‐bromo ethenylsulfones with organoboron reagents is reported.